Study On Balance Sheet and Least Possible Risk (International Journal of Innovative Research in Engineering & Management, 2021)
A balance sheet is a financial accounting overview of an  individual's or organisation 's financial balances, whether it’s a  sole proprietor, commercial partnership, corporation,  commercial limited corporation, or another entity such as the  governments or a not-for-profit. A receivables, obligations, and  ownership equity are stated as of a certain date, such as the  fiscal year's end. A "picture of a corporation's financial status"  is how a balancing sheet is commonly referred to. The  balancing sheets is the only ones of the four basic financial  statements that refers to a specific moment in time throughout  a company's fiscal year. In this review article, we look at the  overview of a balance sheet, the components of a balance sheet,  as well as the benefits and drawbacks of a balance sheet. The  future scope of the balance sheet is that Stakeholders will be  able to review the balance sheet to understand the company's  liquidity status and business performance.
Keywords: Assets; Balance sheet; Company; Risk Financial